Empowering the competitiveness of Asnaf Rural Zakat Entrepreneurs Policy: National Development Aspirations 2030 - Mohd Afandi Mat Rani; Zarith Sofia Jasmi; Mohd Saleh Abbas; Albert Feisal Ismail; Habibah @ Artini Ramlie; Mohd Norazmi Nordin; Pg Ismail Pg Musa (ResearchTrentz, 2022)
Entrepreneurship is an area that can change the landscape of people’s lives in a country. This activity not only can make a huge contribution to individuals but can also impact the development of a country. To achieve this, the government has formulated various policies making entrepreneurship a national priority. Therefore, the study aims to outline the agenda of national development in 2030 in strengthening the competitiveness of entrepreneurship especially for rural entrepreneurs. This qualitative study was conducted using data collection and data analysis methods. The method of data collection is done through library research. The data obtained were analysed based on inductive and deductive methods to obtain the results. The analysis has outlined the competitiveness of rural entrepreneurs to be included in the government agenda such as National Entrepreneurship Policy 2030, Sustainable Development Goals (SDGs), Shared Prosperity Vision 2030, Rural Development Policy, Rural Development Harapan Blueprint 2018-2023, Small and Medium Enterprise Master Plan 2012-2020. However, the key challenge in making this agenda successful is to change the mindset of the rural community to be ready to accept and make any changes to create an entrepreneurial community by 2030.